The Planning Process of the “WISE ASSIST”Daily Living System for Senior Citizens - Umi Nashwah Mohd Zainiu; Nurdiana Azizan (USIM Press, 2024)
Malaysian Journal of Science Health & Technology, Volume 10 Issue 1 Page (26–38)